Decarbonisation of manufacturing operations: a case study in automotive manufacturing - Andreas Serino Olander; Lucas Albuquerque Wolf; Lena Moestam; Mélanie Despeisse (Production and Manufacturing Research: An Open Access Journal)
In response to the climate crisis, companies are increasingly committed to lowering their emissions. Previous studies have investigated climate mitigation strategies in carbon-intensive industries. However, emissions from less carbon-intensive sectors must also be addressed to reach net-zero goals. This study focuses on manufacturing operations and proposes a three-step approach to initiate industrial decarbonisation activities. Technological solutions across six strategies were investigated: fuel shift, electrification, carbon capture, process efficiency, technology substitution, and circularity. An in-depth case study at a multinational automotive manufacturing company was conducted with 16 semi-structured interviews to qualitatively evaluate technological solutions, highlighting implementation challenges from the case company’s perspective. While there is no universal set of priorities for decarbonisation, the proposed three-step approach can help companies organise their decarbonisation activities more effectively. Finally, we suggest further work to tackle current and emerging challenges potentially hindering decarbonisation efforts in less carbon-intensive sectors.